Circ_0058106 promotes proliferation, metastasis and EMT process by regulating Wnt2b/β-catenin/c-Myc pathway through miR-185-3p in hypopharyngeal squamous cell carcinoma - Ce Li; Wenming Li; Shengda Cao; Jianing Xu; Ye Qian; Xinliang Pan; Dapeng Lei; Dongmin Wei (Cell Death and Disease, 2021)
Abstract Hypopharyngeal squamous cell carcinoma (HSCC) accounts 95% of hypopharyngeal cancer, which is characterized by high early metastasis rate and poor prognosis. It is reported that circular RNA is involved in the occurrence and development of cancer; however, the role of circRNA in hypopharyngeal cancer has little been investigated. We performed hypopharyngeal carcinoma circRNA microarray and qRT-PCR verification. The results showed circ_0058106 expression level was significantly upregulated in tumor tissues than in corresponding normal tissues. We found that circ_0058106 upregulation promoted proliferation, migration and invasion of HSCC cells, while knockdown of circ_0058106 inhibited proliferation, migration and invasion of HSCC cells both in vitro and in vivo. Bioinformatics predicted circ_0058106 may interact with miR-185-3p. We verified circ_0058106 directly bound miR-185-3p and downregulated miR-185-3p expression by using dual-luciferase reporter assay and qRT-PCR. Moreover, we proved circ_0058106 promoted HSCC cells tumorigenesis and EMT process by regulating Wnt2b/β-catenin/c-Myc pathway via miR-185-3p. In conclusion, our findings firstly confirmed the carcinogenic effect of circ_0058106 in promoting HSCC cells tumorigenesis, metastasis, invasion and EMT process by regulating Wnt2b/β-catenin/c-Myc pathway through sponging miR-185-3p, indicating that circ_0058106 may be a new therapeutic target and prognostic marker for HSCC.